TAFSIR JAMA’I UNTUK PENCERAHAN UMMAT - Syamsul Hidayat (Kopertais Wilayah X Jawa Tengah, 2017)
This study aims to examine the interpretation of At-Tanwir, published by theMuhammadiyah Central Executive, by looking at his position in the map of the study of Qur’anic commentary in present-day Indonesia.  e study focused on the form, method and style of interpretation used by the interpretation.According to several studies conducted by Howard M. Federspiel, Islah Gusmian and Ahmad Arif Junaidi, the study of the Qur’anic commentary in Indonesia that has grown long enough, even since the entry of Islam in Indonesia, begins with a study of the Arabic tafsir classic, later developed into the writing of the tafsir books in Arabic, Malay (Indonesian), as well as interpretations in several regional languages. Diff erent forms of interpretation, methods and styles. However, more is the interpretation of bil ra’yi, by the method of ijmali and tahlily, by combining linguistic complexities, legal fiqh, theology, and social culture literature. Nevertheless, there is also a very limited number of maudhu’i (tematic) interpretations. In general, the book of exegesis is written by individuals (tafsir fardi) and a little interpretation written by the team in institutional (tafsir jama’i).Tafsir at-Tanwir attempts to interpret the Quran with the principle of responsiveness, awakening the dynamics, generating ethos: the ethos of worship, the economic ethos,the social ethos, and the scientië c ethos. However, the weakness of this Tafsir At-Tanwir does not or has not expressed the characteristics of this exegesis as compared with other interpretations as it is done by the interpretation of the Ministry of Religious Aff airs, which provides a description in the Preamble which is recorded in a special volume, so that the reader must be careful in groping model and content of this book of exegesis.